Spesies Mollusca di Ekosistem Mangrove Kecamatan Baitussalam Kabupaten Aceh Besar sebagai Referensi Pendukung Materi Keanekaragaman Hayati - Aisyah Idris; Miszora Novita; Samsul Kamal (Biotik, 2018)
Mollusca is the second largest phylum of invertebrate animals that has high adaptability. One of Mollusca's habitats is the mangrove ecosystem in Baitussalam District, Aceh Besar. There were very little data regarding the type and diversity of Mollusca in the mangrove ecosystem area of Baitussalam Subdistrict, Aceh Besar, after the tsunami in 2004. A study is needed considering that the data can be used as a database and supporting reference for biodiversity material in schools. This study was carried out to; 1) Identifies the types of Mollusca in the mangrove ecosystem in Baitussalam District, Aceh Besar; 2) Determines the output of this study as a reference for supporting biodiversity learning; and 3) Finds out the feasibility of the output as supporting reference for biodiversity material. Data collection was performed by line transect and quadrant transect method with purposive sampling. Data was analyzed with qualitative and quantitative analysis. The results of the study revealed that there are 29 types of Mollusca consisting of Gastropods and Bivalves. The output is in the form of a national standard textbook that can be used as a reference for supporting biodiversity learning. The book feasibility test obtained a total score of 95.6%. The conclusion is that there are 29 types of Mollusca and the output is a national standard textbook that are very feasible to be recommended as a supporting reference for biodiversity material.